ANALYSIS OF THE IMPACT OF VSAT AND FIBER OPTIC ACCESS MEDIA USAGE ON THE NETWORK PERFORMANCE OF BANK SYARIAH INDONESIA (BSI) ATMS IN LINTASARTA, KALIMANTAN AREA - Putri, Dita My Yani; Septima, Uzma; Yustini , Yustini (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
The ATM communication network in the Kalimantan region utilizes two main access media: VSAT and Fiber Optic. VSAT is used in remote areas with limited infrastructure, while Fiber Optic is implemented in urban areas with better connectivity. This study aims to analyze the performance of both access media based on bandwidth, delay, and packet loss parameters across 20 ATM samples of Bank Syariah Indonesia (BSI) in Kalimantan. The results indicate that VSAT has higher latency and is more susceptible to weather conditions, although it still provides an average SLA above 99%. Meanwhile, Fiber Optic demonstrates more stable performance with low latency and high speed but is vulnerable to physical disruptions such as cable cuts. To enhance network quality, bandwidth optimization for VSAT and Fiber Optic infrastructure expansion into semi-urban areas are necessary.